Peran Etika dan Tanggung Jawab Sosial dalam Bisnis Internasional - Nurasha Alfahira; Putri Suci Ramadhani; Desi Fitri Yani Sembiring; Syafri Fadillah Marpaung (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Business is an activity carried out by individuals or groups that involves the process of making, selling, purchasing or exchanging goods or services with the aim of generating profits. The aim of this research is to describe or explain literature studies regarding the role of ethics and social responsibility in business. This research method uses a qualitative research method using a literature review approach or based on literature review through book review and journals. The research steps start from collecting articles, reducing articles, discussing and concluding. The results of this research show that ethics and responbility in business have the same role which aims to improve the company’s image to develop the company.